2013
DOI: 10.1016/j.juro.2012.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroenteric Anastomotic Strictures After Radical Cystectomy—Does Operative Approach Matter?

Abstract: Of the patients 9.4% were diagnosed with benign ureteroenteric anastomotic stricture after radical cystectomy with no significant difference in the risk of diagnosis by surgical approach. No patient or disease specific factor was independently associated with an increased risk of stricture diagnosis. Ureteroenteric anastomotic stricture is likely related to surgical technique. Continued efforts are needed to refine the technique of open and robot-assisted laparoscopic radical cystectomy to minimize the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 26 publications
5
62
0
4
Order By: Relevance
“…Treatment of these strictures represents a particular challenge for urologists due to their relatively high prevalence, recurrences rates, and inherent morbidity [16]. Advances in endourology have given rise to alternative treatment modalities such as stent insertion, balloon dilation, and cold ureterotomy, each with varying success rates.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of these strictures represents a particular challenge for urologists due to their relatively high prevalence, recurrences rates, and inherent morbidity [16]. Advances in endourology have given rise to alternative treatment modalities such as stent insertion, balloon dilation, and cold ureterotomy, each with varying success rates.…”
Section: Discussionmentioning
confidence: 99%
“…По неко-торым предположениям, фактором риска развития этого осложнения является избыточная диссекция при формировании экстракорпорального анастомоза, и указанная выше частота отображает данные иссле-дований, в которых анастомоз накладывался экстра-корпорально. Однако в недавней серии цистэктомий, представленных C. B. Anderson и соавт., разница в час-тоте стриктур УИА при открытой операции и лапаро-скопических техниках, несмотря на некоторое разли-чие (8,5 и 12,6 % соответственно), не является достоверной (p = 0,21) и уменьшается по мере улучше-ния техники операции [30].…”
Section: Discussionunclassified
“…Anderson et al 1 noted that stricture rates are often under-reported owing to variable follow-up durations and nonstandardized use and frequency of urinary tract imaging. The majority of strictures occur within 2 years of surgery, with median time to diagnosis in the literature reported as 7-25 months after surgery 7,8,[11][12][13] , although they can occur as late as 160 months postoperatively 14 .…”
Section: Incidencementioning
confidence: 99%